Beak trimming in japanese quails at initial phase is an alternative to reduce the negative effects of feather pecking - Cruvinel, Jéssica Moraes (2022)
Regarding the lack of standardized methods for beak trimming to reduce feather pecking in Japanese quail, the present study aimed to compare two ages and 3 methods of beak trimming, evaluating the performance, egg quality and feather pecking. One-day-old Japanese quails (n = 770; 22 birds cage-1), at the initial phase, and 36-day-old (n = 630; 18 birds cage-1), at the production phase, were assigned to a completely randomized design, consisting of 7 treatments with 5 replicates. The treatments were: non-trimmed (NT), cauterization of approximately 1/3 at 14 days-of-age (CAUT 14) and at 28 days-of-age (CAUT 28), moderately trimmed to approximately 1/3 beak at 14 days-of-age (MOD 14) and at 28 days-of-age (MOD 28), severely trimmed to 1/3-1/2 beak at 14 days-of-age (SEV 14) and at 28 days-of-age (SEV 28). Data were analyzed using Minitab®. The results indicated that beak trimming methods applied did not influence the performance and egg quality. Quails subjected to MOD 28 and SEV (14 and 28) presented lower feed conversion per egg mass compared to NT. However, MOD 14 and SEV were more efficient in preventing feather pecking behavior.